Sources of polycyclic aromatic hydrocarbons exposure and their effects on glycolipid metabolism in pregnant women and their newborn in Haikou City, China - Cheng, Xiaomei; Gao, Haifeng; Li, Qiaojun; Zhang, Naifan; Lu, Ying (Frontiers in Public Health, 2025)
BackgroundPolycyclic aromatic hydrocarbons (PAHs) are a class of large organic compounds that persist in the environment and are classified as an important subset of persistent organic pollutants (POPs). This study aimed to assess PAH exposure in pregnant women and newborns in Haikou City, China, and evaluate their impact on glycolipid metabolism.MethodsA total of 300 pregnant women and their newborns were selected for the study between May 2022 and December 2023. Data on lifestyle and dietary habits were collected, and PAH levels in venous blood and umbilical cord blood were measured using gas chromatography-mass spectrometry. Glycolipid metabolism indicators, including fasting plasma glucose (FPG), triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL), were also measured. Correlation and regression analyses were conducted to explore the relationships between PAH exposure and metabolic indicators.ResultsThirteen PAHs were detected in both maternal and cord blood. The median concentrations of ΣPAHs (the total concentration of the 16 detected PAHs) were 11.211 μg/L in maternal blood and 10.921 μg/L in newborns. Significant correlations were observed between PAH exposure and glycolipid metabolism, with PAH exposure linked to reduced levels of TC and TG. Factors such as proximity to roads, cooking fuel type, and dietary habits influenced PAH levels. Higher education levels were associated with lower PAH concentrations, whereas living near roads and using gas as cooking fuel increased exposure.ConclusionThere is a notable risk of PAH exposure in pregnant women and newborns in Haikou, influenced by environmental and lifestyle factors. PAH exposure during pregnancy may affect glycolipid metabolism in both mothers and newborns, highlighting the need for interventions to reduce exposure.